FAKTOR DOMINAN DALAM MENINGKATKAN KUNJUNGAN ANAK DI BAWAH DUA TAHUN (BADUTA) - Haris, Lala; M Ridwan, M Ridwan; Ibnu, Ismi Nurwaqiah (Poltekkes Kemenkes Bengkulu, 2023)
Posyandu as a facility for monitoring the growth and development of toddlers and nutritional services has not been utilized optimally. Jambi City Health Profile Data at the Paal Merah I Health Center in 2021 (27,78%) shows that the number of visits is still far from the National Target of 87%. The purpose of this study was to determine the relationship between the characteristics of mothers under two years old (education and employment) to mothers under two years old in the working area of ​​the Paal Merah I Health Center. The research design was cross-sectional quantitative analytic. The sample size is 86. The independent variables in this study are education and employment, while the dependent variable is posyandu visits. Data obtained by filling out questionnaires by respondents. Data analysis used univariate and bivariate tests (Chi-Square). the results of the study found that mothers under two had low education (52,3%), then mothers under two who did not have a job (90,7%), and mothers under two who visited posyandu well (53.5%), there were factors related to posyandu visits is education (P= 0,003), and employment (P=0,023) with posyandu visits. there is a relationship between education and work with posyandu visits to mothers under two years old in the Working Area of ​​the Paal Merah I Health Center, Jambi City.